Promotion of growth and biological state of microalgae-bacteria consortia during swine wastewater treatment doped with nano-sized iron - Yang-Yan Wang; Hai-Xiang Cheng; Pin Wang; Rui Fan; Long-Zao Luo; Guo-Hui Lin; Guang-Ming Tian (Scientific Reports)
Abstract Microalgae-bacteria consortia is an effective bioremediation technique employed for treating piggery effluent, and how to enhance its purification performance has always been a research hotspot. This study aims to investigate the growth and biological state of microalgae-bacteria consortia during swine wastewater treatment doped with nano-sized iron including Nano-ZVI and Nano-Fe3O4. Results showed that the addition of nano-sized iron was more conducive to microalgal growth and pollutant removal from swine wastewater, especially the addition of Nano-ZVI, in which the microalgal biomass was 31.14% higher than that of the control, and the removal rates of NH4 +-N, TN, TP and COD increased to 99.55%, 61.57%, 91.86%, and 49.24%, respectively. The removal rates of Cu and Zn were 93.12% and 99.89%, respectively, after four days of treatment. The addition of Nano-ZVI significantly increased the relative abundance of Bacteroidetes and functional genera, such as Flavobacterium, Brevundimonas, Bacillus, and Hydrogenophaga. 8 metabolic pathways were significantly upregulated compared with the control, encompassing important biochemical processes such as biosynthesis, signal transduction, and energy production, which are closely related to microalgal activity and nutrient absorption. These findings provide scientific guidance for the enhance of microalgae-bacterial consortia in wastewater treatment doped with nano-sized iron.